Pyrolysis of waste treatment sludge from a polymer manufacturing company - Benitez, Arnold B. (Animo Repository, 1997)
Pyrolysis of sludge using the Bench Scale Pyrolyzer is conducted at temperatures of 300, 400, 500 and 600 degrees Centigrade. The objective is to study the behavior and characteristics of sludge during pyrolysis. It was found that product yields and composition are strongly affected by pyrolysis temperature, and the particle size contributed to a small extent. Generally, highest weight loss and liquid production was obtained when pyrolysis temperature was 500 degrees Centigrade. The yield of liquid product and weight loss was not significant at pyrolysis temperature of 300 degrees Centigrade. A thermogravimetric analyzer was used to determine the effect of heating rate (10, 20, 50, 75 degrees Centigrade per minute) on weight loss of sludge and on the kinetics of decomposition. Highest weight loss was obtained at heating rate of 50 degrees Centigrade per minute. A first order decomposition for the four heating rates considered was obtained when Coats and Redfern method was used to analyze the data. However, lower heating rate (10 & 20 degrees Centigrade per minute) resulted in first order decomposition and higher heating rate (50 & 75 degrees Centigrade per minute) resulted in second order decomposition when analyzed using the general equation.